Phoenix 15 May 1969 - San Francisco State University - Journalism Department (San Francisco State University - Journalism Department, 1969)
Phoenix is a weekly laboratory newspaper published during the regular school year by the Department of Journalism at San Francisco State College. The editorial content does not necessarily reflect the policies or opinions of the Department of Journalism or College administration, although ultimately Journalism faculty does assume responsibility. Managing editor Lary Maatz and news editor John Keane. The Phoenix spotlighted campus news and events and includes advertisements.